Sources of Stress and Coping Behaviors among Nursing Students Throughout Their First Clinical Training - Dalia Toqan MSN, PhD; Ahmad Ayed MSN, PhD; Malakeh Z. Malak MSN, PhD; Bahaaeddin M. Hammad MSN, PhD; Mohammed ALBashtawy MPH, PhD; Mohammed Hayek MSN, PhD; Imad Thultheen MSN, PhD (SAGE Publishing, 2023)
Introduction Clinical training allows nursing students to acquire and strengthen their psychomotor abilities, which is an important component of nursing education. The clinical components of nursing training programs were much more demanding than the academic ones. Purposes The purpose of this study was to examine sources of stress-related and coping behaviors during first clinical training among nursing students in the Arab American University. Methods The study was cross-sectional and conducted with a convenience sample of 266 participants of nursing students. Data collection was performed by "Perceived Stress Scale and the Coping Behavior Inventory." The data were analyzed by using the descriptive, that is, frequency and percentage, mean, and standard deviation. Results The results revealed that the perceived stress mean was 41.2 ( SD  = 19.5). The main stressors were taking care of the patients ( M  = 11.4 ± 0.85) and teachers and nursing staff ( M  = 8.32 ± 5.3). Coping behaviors mean was ( M  = 29.0 ± 15.2). The main coping behavior was problem-solving ( M  = 9.5 ± 5.6). Conclusion The study confirmed that students perceived moderate levels of stress in their first clinical training, and the most common sources of stress were taking care of the patients and teachers and nursing staff. However, the main coping behavior was problem-solving.